INFORMATION VISUALIZATION ON THE BASE OF HIERARCHICAL GRAPHS - Kasyanov, Victor N.; Kasyanova, Elena V. (Matematichki Bilten, 2015)
Graphs are the most common abstract structure encountered in computer science and are widely used for abstract information representation. In the paper, we consider a practical and general graph formalism called hierarchical graphs. It is suited for visual processing and can be used in many areas where the strong structuring of information is needed. We present also the Higres and Visual Graph systems that are aimed at supporting of information visualization on the base hierarchical graph modes.